Tinjauan Hukum Humaniter Internasional terhadap Serangan Pemerintah Suriah di Ghouta Timur pada Februari 2018 - Gilang Bima Sakti; Sri Lestari Rahayu (Faculty of Law Universitas Sebelas Maret, 2019)
The humanitarian crisis due to the armed conflict between President Bashar Al-Assad’s government in Syria and residents in the town of Ghouta Timur is a serious concern for the community and international organizations. Moreover, attacks from the Syrian government caused many casualties in the form of civilians, so the Syrian government was also considered to heed international humanitarian law, and could be categorized as war crimes and crimes against humanity. This study aims to determine the arrangements of international humanitarian law against the attacks of the Syrian government in Eastern Ghouta and to know the enforcement of international humanitarian law against violations of the laws of war carried out by the Syrian Government in Eastern Ghouta. The legislation used as a reference includes the Hague Convention of 1907, the Geneva Convention of 1949; and Additional Protocols in 1977. Observations show that Syria was a country which only ratified several regulations relating to international humanitarian law, namely the Geneva Conventions of 1949, Additional Protocol I of 1977, and the Chemical Weapons Convention of 1993. Regulations on humanitarian law against Syrian attacks under the Convention I and Geneva IV Convention In 1949 had several articles governing violations of law committed by the Government of Syria, amounting to 11 Articles. Whereas according to Additional Protocol I, there are several Articles related to violations that occur in Syria, amounting to 7 Articles. The UN Security Council must establish an ad-hoc international court consisting of several judges, public prosecutors and court clerks from various countries. This court must be formed with the authority to try violations of humanitarian law in Syria because national law and justice in Syria do not want to try the accused. In addition to establishing a criminal court for the case of Syria, the United Nations and the international community have the authority to control the Security Council’s decision to anticipate the political elements of the veto that are used by some permanent members of the Security Council to revoke resolutions to end the war in Syria. The UN organization can use low-scale military forces based on the Responsibility to Protect principle, if the UN Security Council as a representative of the international community fails to bring the accused and prosecute before an international court of justice.